2005
DOI: 10.1681/asn.2005010031
|View full text |Cite
|
Sign up to set email alerts
|

Renal Phenotype of UT-A Urea Transporter Knockout Mice

Abstract: The urea transporters UT-A1 and UT-A3 mediate rapid transepithelial urea transport across the inner medullary collecting duct (IMCD). In a previous study, using a new mouse model in which both UT-A1 and UT-A3 were genetically deleted from the IMCD (UT-A1/3 Ϫ/Ϫ mice), we investigated the role of these transporters in the function of the renal inner medulla. Here

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
113
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(127 citation statements)
references
References 44 publications
12
113
1
1
Order By: Relevance
“…It was shown recently in transgenic mice with a selective deficiency in UT-B (the urea transporter protein expressed in descending vasa recta and red blood cells) that lack of UT-B in normal conditions leads to a 44% elevation in plasma urea and to a 25% decrease in urea clearance (29). Recently, it was suggested that just like for uric acid, an active urea secretion does exist somewhere along the renal tubule (1,30). An age-related decrease in urea secretion could be another possible mechanism to explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown recently in transgenic mice with a selective deficiency in UT-B (the urea transporter protein expressed in descending vasa recta and red blood cells) that lack of UT-B in normal conditions leads to a 44% elevation in plasma urea and to a 25% decrease in urea clearance (29). Recently, it was suggested that just like for uric acid, an active urea secretion does exist somewhere along the renal tubule (1,30). An age-related decrease in urea secretion could be another possible mechanism to explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…For testing of this hypothesis, the urinary concentrating function of UT-A1/3 Ϫ/Ϫ mice on three different levels of dietary protein intake was examined in a series of metabolic cage studies ( Figure 4) (37,42). With free access to water, UT-A1/3 Ϫ/Ϫ mice that were fed either a standard-protein (20% protein by weight) or high-protein (40%) diet had a significantly greater fluid intake and urine flow than wild-type controls, resulting in a decreased urine osmolality.…”
Section: Role Of Imcd Urea Transporters In the Urinary Concentrating mentioning
confidence: 99%
“…The conclusion from these data is that the role of IMCD urea transporters in water conservation is to prevent a urea-induced osmotic diuresis. Adapted from data in references (37,42).…”
Section: Accumulation Of Nacl In the Inner Medulla: Role Of Imcd Ureamentioning
confidence: 99%
“…The renal countercurrent mechanisms involve intrarenal urea recycling facilitated by urea transporters (UTs) expressed in renal tubule epithelial cells (UT-A, encoded by the SLc14A2 gene) and renal vasa recta microvessels (UT-B, encoded by the SLc14A1 gene). [3][4][5][6][7] Phenotype analysis of knockout mice lacking UT-B 8,9 or various UT-A isoforms [10][11][12] has provided evidence for the involvement of UTs in the urinary concentrating mechanism, subject to the caveat that gene knockout may produce off-target effects such as compensatory changes in the expression of non-UT transport proteins. 13,14 Although UT function has been studied mainly in the kidney, UTs are also expressed in erythrocytes as well as the testis, brain, heart, and urinary bladder.…”
mentioning
confidence: 99%